Comparison of antiplatelet activity of garlic tablets with cardio-protective dose of aspirin in healthy volunteers: a randomized clinical trial - Mojtaba Shafiekhani; Pouya Faridi; Javad Kojuri; Soha Namazi (Avicenna Journal of Phytomedicine, 2016)
Objective: Some of the adverse effects of aspirin including peptic ulcers, gastrointestinal bleeding and aspirin resistance compelled researchers to find a suitable alternative with fewer adverse effects. In this clinical trial, we aimed to find the effective antiplatelet dose of garlic. Materials and Methods: This randomized controlled clinical trial (RCT) was conducted on 62 healthy volunteers of 20-50 years old. All volunteers used 80 mg aspirin per day for 1 week and at the end of this time, platelet aggregation (PA) induced by 4 agonists acting in aggregation pathway including adenosinediphosphate (20 μmol/l), epinephrine (20 μmol/l), collagen(0.19 mg/ ml) and arachidonic acid (0.5mg/ ml) was measured by Light Transmittance Aggregometry (LTA) in all participants. After one month washout period, volunteers were randomized into 3 groups and each received 1, 2 or 3 garlic tablets (1250 mg) a day for 1 month. After one month, PA was examined in all groups. Results: The mean ±SD of the age of all volunteers was 28.60 ± 9.00 years. In addition, 52.00 % of our volunteers were male and 48.00% of them were female. Garlic tablet didnot have significant effect on PA at any dose. However, 30% of volunteers in the group that used 3 garlic tablets/day reported adverse effect (i.e. bleeding). No significant association between sex, age and PA was observed. Conclusion:  In this study, we were unable to determine the effective anti-platelet dose of garlic which that could be equal to that of aspirin anti-platelet activity, as assessed LTA method.